2008
DOI: 10.1016/j.bbi.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced differences in primary and secondary resistance against bacterial sepsis corresponds with diverse corticotropin releasing hormone receptor expression by pulmonary CD11c+ MHC II+ and CD11c− MHC II+ APCs

Abstract: Stress responses have been associated with altered immunity and depending upon the type of stressor, can have diverse effects on disease outcomes. As the first line of defense against potential pathogens, alterations in cellular immune responses along the respiratory tract can have a significant impact on the manifestation of local and systemic disease. Utilizing a murine model of respiratory pneumonia, the current study investigated the effects of restraint stress on the induction of primary and secondary imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 76 publications
6
20
0
Order By: Relevance
“…NE attenuates overall disease progression in experimental stress models of pneumococcal pneumonia (Gonzales et al, 2008), a finding that is in contrast to results with other pathogens where disease is enhanced (Bansal et al, 2007;Cogan et al, 2007;Hegde et al, 2009;Scheckelhoff et al, 2007;Vlisidou et al, 2004). In this study, we identified that at least one interface between NE and the bacterial-host interaction is at the initial stage of pneumococcal adherence to epithelial surfaces.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…NE attenuates overall disease progression in experimental stress models of pneumococcal pneumonia (Gonzales et al, 2008), a finding that is in contrast to results with other pathogens where disease is enhanced (Bansal et al, 2007;Cogan et al, 2007;Hegde et al, 2009;Scheckelhoff et al, 2007;Vlisidou et al, 2004). In this study, we identified that at least one interface between NE and the bacterial-host interaction is at the initial stage of pneumococcal adherence to epithelial surfaces.…”
Section: Discussionmentioning
confidence: 41%
“…The interaction of NE and pneumococcal pneumonia has been investigated using an immobilization stress model that increases plasma NE levels (Kvetnansky, 2004). In contrast to other infections, increased NE was associated with less pneumococcal invasion from lung to blood and lethality was delayed (Gonzales et al, 2008). This suggests that, unlike findings with many infections, the interaction of NE and pneumococci leads to less invasion and improves outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no previous reports of stress on these parameters of the NALT, other studies have found a reduction in the size of primary lymphoid organs (e.g., the thymus) and secondary nodes and spleen (e.g., the mesenteric lymphoid) [46][47][48][49][50]. Therefore, it is possible that the NALT of Balb/c mice is more resistant to the effects of stress (e.g., apoptosis) than other lymphoid organs, which are modified significantly with short-term and long-term restraint stress protocols [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…However, given the stress of the gavage procedure and the possibility for esophageal tearing, it is important that this assumption is actually tested [33, 35]. Stress has a number of physiological effects in mice that could potentially impact microbiological and immunological studies [38, 41, 44]. Further, the possibility that a pathogen is introduced to the bloodstream or lung during the gavage procedure could also impact the kinetics of infection and subsequent immune response [57, 60].…”
Section: Discussionmentioning
confidence: 99%
“…However, a major drawback to this method is that the gavage needle has the potential to damage the esophageal lining, raising some concern that bacteria could use experimentally-induced abrasions to access the host via an unnatural route [8, 32–34]. In addition, the restraint and manipulation required for effective oral gavage dosing induces significant stress in experimental animals [33, 35, 36], which could potentially impact the immune response [3740] and/or susceptibility to infection [4144]. Taken together, although oral gavage is an effective means of oral infection, the procedure itself has the potential to affect the route of bacterial entry and the subsequent host response.…”
Section: Introductionmentioning
confidence: 99%